Photoactivity of Ag/TiO2 Microsphere by One-Step Hydrothermal Method - Zhang, Jucheng; Bai, Ruyan; Zhai, Fengrui; Duan, Yanmei; Zhang, Qin; Zhao, Huahua; Huang, Qiong; He, Ying (Asian Journal of Chemistry, 2015)
Ag/TiO2 microsphere photocatalyst was prepared via one step hydrothermal method and prepared catalyst was used for photodegradation of rhodamine B under visible light. The Ag/TiO2 catalyst was characterized through X-ray diffraction (XRD) and scanning electron microscope (SEM). The results showed Ag was uniformly distributed in the titanium matrix. The 6 % Ag doped TiO2 catalyst had the higher photoactivity than other proportion to degrade rhodamine B 86.6 % within 60 min under visible light. The Ag doped TiO2 also had the good activity under solar light cut off UV light.